2020
DOI: 10.1002/j.2334-5837.2020.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Tool for Collaboration and Knowledge Sharing of Customer Needs in the Conceptual Phase

Abstract: This paper aims to research how the use of an interactive tool can facilitate collaboration, knowledge sharing and enhance the understanding of customer needs in conceptual phase at a global shipbuilding company. An effective conceptual phase depends on collaboration and mutual understanding of customer needs to capture customer requirements and transform them into a base of design‐document. Lack of early common understanding can result in increased project cost or in worst‐case loss of contract. We used actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In our former research, we identified that the industry needs to support rapid learning of systems knowledge through concept exploration, early validation, and knowledge transfer in the concept phase [33]. Furthermore, we explored the use of co-creative methods and tools [21,22,[34][35][36][37][38] to support the Norwegian high-tech industry in achieving their needs. We concluded on eight success criteria inspired by systems and design theories for a new way of working.…”
Section: Introductionmentioning
confidence: 99%
“…In our former research, we identified that the industry needs to support rapid learning of systems knowledge through concept exploration, early validation, and knowledge transfer in the concept phase [33]. Furthermore, we explored the use of co-creative methods and tools [21,22,[34][35][36][37][38] to support the Norwegian high-tech industry in achieving their needs. We concluded on eight success criteria inspired by systems and design theories for a new way of working.…”
Section: Introductionmentioning
confidence: 99%